ANISOTROPY OF MAGNETIC SUSCEPTIBILITY (AMS) IN VOLCANIC FORMATIONS: THEORY AND PRELIMINARY RESULTS FROM RECENT VOLCANICS OF BROADER AEGEAN. - Zananiri, I.; Kondopoulou, D. (Bulletin of the Geological Society of Greece, 2004)
The anisotropy of magnetic susceptibility (AMS) is a physical property of rocks widely used in petrofabric studies and other applications. It is based on the measurement of low-field magnetic susceptibility in different directions along a sample. From this process several scalar properties arise, defining the magnitude and symmetry of the AMS ellipsoid, along with the magnetic foliation, namely the magnetic fabric. Imaging the sense of magma flow in dykes is an important task for volcanology; the magnetic fabric provides a fast and accurate way to infer this flow direction. Moreover, the AMS technique can be used in order to distinguish sills and dykes, a task that is almost impossible by using only field observations. Finally in the case of lava flows, the method can be applied to define the local flow conditions and to indicate the position of the "paleo" source region. However, this technique is quite new in Greece. Some preliminary results from volcanic formations of continental Greece and Southern Aegean are presented (Aegina, Almopia, Elatia, Gavra, Kos, Patmos, Samos, Samothraki and Santorini).